Comparison of MMF efficacy and safety in paediatric vs. adult renal transplantation: subgroup analysis of the randomised, multicentre FDCC trial - Höcker, Britta; Gelder, Teun van; Martin-Govantes, Juan; Machado, Paula; Tedesco, Helio; Rubik, Jacek; Dehennault, Maud; Garcia Meseguer, Carmen; Tönshoff, Burkhard (Nephrology, dialysis, transplantation, 2011)
Background. Mycophenolate mofetil (MMF) is widely used for immunosuppressive therapy in renal transplantation, but comparative data regarding efficacy and safety in paediatric vs. adult kidney allograft recipients in one and the same study are lacking.Methods. We therefore performed this subgroup analysis of the FDCC trial, a 12-month, prospective, randomised study, comparing fixed-dose (FD) with concentration-controlled (CC) MMF dosing in paediatric and adult renal transplant recipients. Sixty-two paediatric and 839 adult de novo patients in 19 countries were randomised 1:1 to receive fixed-dose or concentration-controlled MMF therapy in combination with calcineurin inhibitors and corticosteroids.Results. Both patient and allograft survival proved to be excellent in paediatric patients (98.4% and 90.3%) and adults (96.8% and 95.0%). The rates of biopsy-proven acute rejections (BPAR) and treated acute rejection episodes (ARE) were comparable between paediatric (12.9% and 17.7%) and adult patients (15.5% and 20.7%). Transplant function at 12 months post-transplant was similar in paediatric (67.8 ± 45.6 mL/min/1.73 m²) and adult recipients (64.7 ± 23.3 mL/min/1.73 m²). Children < 6 years (n = 10) exhibited a numerically higher frequency of leucocytopaenia (20%), diarrhoea (40%) and weight loss (10%) than older children (6-18 years; 5.8%, 28.8% and 1.9%) and adults (16.1%, 24.7% and 1.5%). On the whole, the percentage of patients who experienced adverse events causing interruption of MMF therapy were numerically lower in children (4.8%) than in adults (12.5%).Conclusions. The overall efficacy and tolerability of MMF appear to be comparable between paediatric and adult patients. Further studies are needed to validate these results.
Advance access publication 28 July 2010
Gesehen am 04.08.2022